REASSESSING THE USE OF IMAGERY OF THE BEAST, THE SEA, AND THE SEVEN HEADS IN REVELATION 13 - Steven Steven (Jurnal Amanat Agung, 2026)
A line of scholarship on Revelation assumes that its imagery blends elements from the Hebrew Bible, ancient myths, and the Greco-Roman world. This study challenges that reasoning by showing that the writer of Revelation not only draws primarily on the Hebrew Bible but also intentionally de-mythologizes its chaos motifs. In Revelation 13, the “sea” is not an autonomous force in cosmic conflict with God but a narrative backdrop for the rise of imperial evil, subverting the standard “sea = chaos” reading. Likewise, the seven heads invert the Hebrew Bible’s symbolic completeness into a counterfeit sovereignty, parodying Rome’s claims to total rule. By foregrounding immediate literary context and socio-political setting over speculative mythic parallels, this article contends that Revelation’s imagery reshapes inherited biblical motifs into a symbolic grammar that equips communities under empire to discern, resist, and hope.